MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI KECEPATAN MENGGUNAKAN MODEL COOPERATIVE TIPE GRUP INVESTIGATION - Nurhakikah, Ulfa; Hayaturraiyan, Hayaturraiyan (LP2M STAI Darul Kamal NW Kembang Kerang, 2021)
Abstract This research was conducted to improve student learning outcomes in the subject of speed mathematics using the Cooperative Type Group Investigation model in class VB MI NW Kalijaga. This type of research is Classroom Action Research (CAR) using quantitative methods, because this data uses numbers, starting from data collection, data interpretation and appearance of results. as many as 14 students. The results of this study can be seen from student learning outcomes, in the pre-cycle there are still many students who have not completed based on KBM (73%), in the pre-cycle there are only five students who have completed (35.7%) with an average score of 56, 8, the highest score was 93 and the lowest score was 30. In the first cycle there was an increase to seven students (50%) who completed KBM, the average value was 63.2, the highest score was 95 and the lowest score was 30. In the second cycle of learning improvement from The 14 students who completed KBM increased again to 10 students (89%), the average score was 75.6, the highest score was 98 and the lowest score was 40.